2017
DOI: 10.4172/2151-6200.1000295
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Practice of Teacher-Student Classroom Interaction in EFL to Develop the Learners’ Speaking Skills in Tullu Sangota Primary School Grade Eight Students in Focus

Abstract: In the process of Second Language Acquisition (SLA), classroom interaction takes an important place. Teachers need to apply appropriate classroom interaction to facilitate language learning in reality since interaction is in the heart of communication in an era of communicative language teaching. Therefore, the purpose of this study was conducted to assess teachers' application of classroom interaction on developing the students speaking skills in Tullu Sangota Primary school grade 8. Specifically, the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
1
21
1
1
Order By: Relevance
“…However, the teacher's perspectives did not correspond with practices in doing group discussions, interviewing each other, providing different examples, and self-repairing. This corresponded with Farrell and Lim, 2005;Chowdhury and Rashid, 2014;Adaba, 2017;Rahman, Singh & Pandian, 2018 studies that revealed disagreement between participants' perspectives and classroom applications.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the teacher's perspectives did not correspond with practices in doing group discussions, interviewing each other, providing different examples, and self-repairing. This corresponded with Farrell and Lim, 2005;Chowdhury and Rashid, 2014;Adaba, 2017;Rahman, Singh & Pandian, 2018 studies that revealed disagreement between participants' perspectives and classroom applications.…”
Section: Discussionsupporting
confidence: 81%
“…These previous studies (e.g., Adaba, 2017;Afrin, 2018, Sundari, 2017Raman, 2017;Rahman, Singh & Pandian,2018;Farrell and Limp, 2005) have evidenced that classroom context (e.g., classroom size and time), students' problems (e.g., shyness, lack of confidence and the low level of English), and teachers (such as, teaching through teacher-centred instruction) are very common factors that influence the teacher's beliefs and practices and should be solved.…”
Section: Chapter Two: Review Of Related Literaturementioning
confidence: 81%
“…Reconocido como un aspecto importante para la adquisición de una lengua, el input lingüístico ha sido un tema recurrente en la investigación, desde hace ya varias décadas, en contextos tanto de segunda lengua como de lengua extranjera. Encontramos, por ejemplo, las investigaciones de Adaba (2017) en Etiopía, Barbee (2013) y Saito y Hanzawa (2016) en Japón, Sivertzen (2013) en Noruega, Utenga et al (2016) en Tanzania, Zainil (2013) en Indonesia, y Zhang (2009) y Wang (2010) en China, por mencionar algunos.…”
Section: Introductionunclassified
“…For learning a foreign language, it is necessary to build mental, emotional and social interactions between teachers and students (Faramarz Zadeh, 2016;Faravani, 2021). Adaba (2017) claimed classroom interaction plays an important role in the process of language teaching and learning by giving learners opportunities to receive the input that is provided by the teacher, learners or material which must be understood by the learners in order to make them involved in the classroom task by providing the output. Interaction in English classroom is in the core of communication in this era of communicative language teaching.…”
Section: Introductionmentioning
confidence: 99%